2021
DOI: 10.3390/vaccines9030235
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Profiling of End Stage Cancer Patients Treated with Immunotherapy

Abstract: Published data suggest that immunotherapy plays a role even in patients with very advanced tumours. We investigated the immune profile of end-stage cancer patients treated with immunotherapy to identify changes induced by treatment. Breast, colon, renal and prostate cancer patients were eligible. Treatment consisted of metronomic cyclophosphamide, low-dose interleukin-2 (IL-2) and a single radiation shot. A panel of 16 cytokines was assessed using automated ELISA before treatment (T0), after radiation (RT; T1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Since the analysis pooled a small cohort of multiple cancer types, this conclusion needs to be interpreted with some caution. 20 A recent Mendelian randomisation study found that genetically predicted higher plasma levels of CCL2 increased the risk of developing PCa, which supports the concept of using CCL2 as a PCa biomarker. 21 However, gene variants causing a problematic increase in CCL2 plasma levels may be too rare to warrant the use of plasma CCL2 levels as a diagnostic biomarker.…”
Section: Discussionmentioning
confidence: 66%
“…Since the analysis pooled a small cohort of multiple cancer types, this conclusion needs to be interpreted with some caution. 20 A recent Mendelian randomisation study found that genetically predicted higher plasma levels of CCL2 increased the risk of developing PCa, which supports the concept of using CCL2 as a PCa biomarker. 21 However, gene variants causing a problematic increase in CCL2 plasma levels may be too rare to warrant the use of plasma CCL2 levels as a diagnostic biomarker.…”
Section: Discussionmentioning
confidence: 66%
“…The 18 cytokines selected in our study are extensively included by other authors in panels aimed to identify prognostic/predictive biomarkers in other solid tumors [24,25]. Moreover, the same cytokines were tested in other cancers by our group, showing to be useful in identifying potential biomarkers [26,27].…”
Section: Discussionmentioning
confidence: 98%
“…Our group has used PCA to identify a cytokinome signature able to discriminate different prognostic groups among end-stage patients affected by different solid tumors [ 44 ] and in breast cancer patients to identify a signature potentially able to select patients for treatment beyond progression [ 45 ]. However, to the best of our knowledge, this is the first study on colorectal cancer using PCA to evaluate a cytokine profile in patients with metastatic disease treated with standard therapy.…”
Section: Discussionmentioning
confidence: 99%